Effect of different crop establishment methods and weed management practices on finger millet (Eleusine coracana L. Gaertn) under rainfed situation - Pradhan, Adikant; Sao, A.; Patel, D.P.; Mukharjee, S.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted at S.G. College of Agriculture and Research Station, Jagdalpur during Kharif season 2011 and 2012 in a spilt plot design with three replications to find out the effect of weed management practices and different crop establishment methods on growth and yield of finger millet (Eleusine coracana L. Gaertn). The sowing methods as main-plot treatment comprised of broad casting, line sowing and transplanting, whereas weed control practices (five) as sub-plot treatments comprised of isoproturon 0.5 kg/ha and oxyflourfen 0.5 kg/ha as preemergence and 2,4-D 750 g/ha applied at 25 days after sowing, weed free and weedy check. The highest yield attributes and yield were recorded under transplanting followed by line sowing. Minimum weed density and dry matter accumulation was found under transplanting. Among the methods of weed control, isoproturon 0.5 kg/ha gave excellent control of weeds and increased the yield attributes, yield, gross returns and B:C ratio